2019
DOI: 10.1016/j.dadm.2019.02.007
|View full text |Cite
|
Sign up to set email alerts
|

The Meta VCI Map consortium for meta‐analyses on strategic lesion locations for vascular cognitive impairment using lesion‐symptom mapping: Design and multicenter pilot study

Abstract: Introduction The Meta VCI Map consortium performs meta-analyses on strategic lesion locations for vascular cognitive impairment using lesion-symptom mapping. Integration of data from different cohorts will increase sample sizes, to improve brain lesion coverage and support comprehensive lesion-symptom mapping studies. Methods Cohorts with available imaging on white matter hyperintensities or infarcts and cognitive testing were invited. We performed a pilot study to test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 76 publications
0
49
0
Order By: Relevance
“…In addition, efforts should be made to increase the sample size of lacunar stroke patients, to increase the reliability and power of the statistical analysis. Creating an international database could provide a promising solution to the small sample sizes which most of the recent literature on lacunar or other mild cortical strokes lists as a limitation, initiated either as a new project or as a branch of a project/consortia like the PLORAS database ( 46 ) or the Meta VCI Map consortium ( 17 ). A range of cognitive tests has been used by different studies making comparison between studies challenging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, efforts should be made to increase the sample size of lacunar stroke patients, to increase the reliability and power of the statistical analysis. Creating an international database could provide a promising solution to the small sample sizes which most of the recent literature on lacunar or other mild cortical strokes lists as a limitation, initiated either as a new project or as a branch of a project/consortia like the PLORAS database ( 46 ) or the Meta VCI Map consortium ( 17 ). A range of cognitive tests has been used by different studies making comparison between studies challenging.…”
Section: Discussionmentioning
confidence: 99%
“…The general impact of infarct location on cognition has been studied in relation to stroke lesion volume ( 13 ), shape ( 14 ), white matter hyperintensity (WMH) volume ( 15 ), post-stroke depression and behavioral disorders ( 16 ). A large multi-center study found that infarcts (i.e., cortical and subcortical) affecting the basal ganglia and internal capsule were associated with impairment of global cognition ( 17 ), in a sample of 878 patients with ischemic stroke. Ischemic strokes' lesions in both brain hemispheres have been associated with lower performances in visuospatial and executive functions ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…20 First, acute infarcts were manually segmented on DWI (97.5%) or FLAIR (2.5%) sequences using in-house developed software built in MeVisLab (MeVis Medical Solutions AG, Bremen, Germany). 21 Next, all scans and the corresponding lesion maps were transformed to the T1 1-mm MNI-152 brain template 22 with the RegLSM tool (www.metavcimap.org/features/software-tools; most recent version described in Weaver et al 23 ). Quality checks of all registration results were performed by one rater (N.A.W.).…”
Section: Generation Of Infarct Mapsmentioning
confidence: 99%
“…Lesion segmentations were subsequently checked and adapted by two experienced raters (N.A.W., J.M.B). Subsequently, images as well as corresponding lesion maps were linearly and non-linearly normalized to Montreal Neurological Institute (MNI-152) space employing the RegLSM image processing pipeline (public code: http://lsm.isi.uu.nl/; Weaver et al, 2019).…”
Section: Neuroimaging Data Preprocessingmentioning
confidence: 99%